Метод решения задачи многоуровневого программирования - Горбачук, В.М.; Ненахова, С.Г. (Теорія оптимальних рішень, 2005)
The solutions to important applied classes of multilevel programming problem are obtained. It is shown the number of levels in such a problem is endogenous. The role of generalized Cournot–Stackelberg–Nash equilibrium introduced earlier is demonstrated. It is shown the Stackelberg oligopoly problem is reduced to a new class of discrete-continuous problems. The instability of Cournot oligopoly is demonstrated.